2004
DOI: 10.1534/genetics.166.2.959
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Genetic Characterization of CMS-SRestorer-of-FertilityAlleles Identified in Mexican Maize and Teosinte

Abstract: Restorer-of-fertility (Rf ) alleles for S-type cytoplasmic male sterility (CMS-S) are prevalent in Mexican races of maize and teosinte. Forty-five Rf alleles from 26 races of maize and 6 Rf alleles from different accessions of teosinte were found to be homozygous viable, consistent with the hypothesis that they are naturally occurring Rf alleles. Mapping and allelism studies were performed to assess the number of genes represented by these 51 alleles. Forty-two of the Rf alleles mapped to the long arm of chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 57 publications
0
15
0
4
Order By: Relevance
“…Gabay- Laughnan et al (2004) reported that 42 restorer alleles for CMS-S in Mexican maize and teosinte mapped to the long arm of chromosome 2; five of them were further mapped to the whp1-rf3 region. These results indicated that rf3 may be a complex locus similar to some disease resistance genes (Li et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Gabay- Laughnan et al (2004) reported that 42 restorer alleles for CMS-S in Mexican maize and teosinte mapped to the long arm of chromosome 2; five of them were further mapped to the whp1-rf3 region. These results indicated that rf3 may be a complex locus similar to some disease resistance genes (Li et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The QTL region in bin 2.09 collocates with a cluster of multiple restorer genes for S-CMS, including the major restorer gene Rf3 (Gabay- Laughnan et al 2004), and Rf8 and Rf*, which restore T-CMS in the presence of Rf2 (Dill et al 1997). The QTL in bins 3.05 and 3.06 are linked to Rf1 of T-CMS in bin 3.04.…”
Section: Partial Restoration Is Inherited Like An Oligogenic Traitmentioning
confidence: 99%
“…The CMS phenotype is a maternally inherited trait caused by incompatibility between the nuclear and cytoplasmic genomes (Ruiz & Daniell, ). Classical genetic studies have reported that CMS is associated with aberrant recombination in the mitochondrial genome (Conde, Pring, Schertz, & Ross, ; Das et al., ; Eckardt, ; Hanson & Bentolila, ; Lee, Muthukrishnan, Sorensen, & Liang, ; Levings & Pring, ; Luo et al., ; Pring, Conde, & Schertz, ; Smith & Chowdhury, ) and fertility was restored by nuclear‐encoded fertility restorer ( Rf ) genes in a number of crop species like rice, soybean, maize, sunflower (Ahmadikhah & Karlov, ; Dong et al., ; Gabay‐Laughnan, Chase, Ortega, & Zhao, ; Yue, Vick, Cai, & Hu, ) including sorghum (Jordan et al., , ; Klein et al., ; Praveen, Suneetha, Umakanth, Patil, & Madhusudhana, ).…”
Section: Introductionmentioning
confidence: 99%